Application of Knowledge and Digital Marketing to the D’Bakulan Business Group and Enye In Sidoarjo City - S. Hardjati; R. R. Prayogo (Nusantara Science and Technology Proceedings)
Empowerment of SMEs in Indonesia the most important part of improving the national economy. The development of SMEs as an effort to empower small businesses to achieve goals in creating a prosperous society. Empowerment is done to form an independent society in the economy. Many of the people who are still experiencing difficulties and obstacles in running their small businesses, including the Joint Business Group D'Bakulan and Enye, which are in the district, Sidoarjo, East Java. Various obstacles and problems that are being faced by KUB are caused by technological advances in presenting interesting products for KUB demands an active role in running a business together with knowledge and information technology in marketing online-based products, namely digital marketing. The joint business group D’Bakulan and Enye is a small community group that conducts joint business activities in the field of food production to meet market demands such as snacks and souvenirs typical of Sidoarjo City. This is in line with Sidoarjo City as a Transit City in East Java including Pantura and has an airport that at any time many migrants visit and buy souvenirs to carry as a typical city of Sidoarjo. Community service activities aim to provide solutions to the obstacles faced by KUB through innovative product FGDs, photoshop product design training and training in using online media to market available products based on digital marketing. Various solutions have been provided through this program such as digital marketing and the creation of innovative products and the creation of blogs to prepare joint business groups in marketing products using digital marketing.